Emerging Trends in the Epidemiology of West Nile and Usutu Virus Infections in Southern Europe - Vilibic-Cavlek, Tatjana; Savic, Vladimir; Petrovic, Tamas; Toplak, Ivan; Barbic, Ljubo; Petric, Dusan; Tabain, Irena; Hrnjakovic-Cvjetkovic, Ivana; Bogdanic, Maja; Klobucar, Ana; Mrzljak, Anna; Stevanovic, Vladimir; et al. (Frontiers in Veterinary Science, 2019)
The epidemiology of West Nile (WNV) and Usutu virus (USUV) has changed dramatically over the past two decades. Since 1999, there have been regular reports of WNV outbreaks and the virus has expanded its area of circulation in many Southern European countries. After emerging in Italy in 1996, USUV has spread to other countries causing mortality in several bird species. In 2009, USUV seroconversion in horses was reported in Italy. Co-circulation of both viruses was detected in humans, horses and birds. The main vector of WNV and USUV in Europe is Culex pipiens, however, both viruses were found in native Culex mosquito species (Cx. modestus, Cx. perexiguus). Experimental competence to transmit the WNV was also proven for native and invasive mosquitoes of Aedes and Culex genera (Ae. albopictus, Ae. detritus, Cx. torrentium). Recently, Ae. albopictus and Ae. japonicus naturally-infected with USUV were reported. While neuroinvasive human WNV infections are well-documented, USUV infections are sporadically detected. However, there is increasing evidence of a role of USUV in human disease. Seroepidemiological studies showed that USUV circulation is more common than WNV in some endemic regions. Recent data showed that WNV strains detected in humans, horses, birds, and mosquitoes mainly belong to lineage 2. In addition to European USUV lineages, some reports indicate the presence of African USUV lineages as well. The trends in WNV/USUV range and vector expansion are likely to continue in future years. This mini-review provides an update on the epidemiology of WNV and USUV infections in Southern Europe within a multidisciplinary “One Health” context.